The Soil of The Seedlings in Greenhouses Heating by Geothermal Energy - Pirnazarov Ilkhom Islamovich (Zien Journals, 2022)
The work depicts the systems which use the sources of geothermal energy for heating greenhouses. The benefit of geothermal energy for conventional purposes is highly acceptable and is an excellent choice of energy source for the greenhouse design. Even though the sources are not available in the whole area of the Republic of Uzbekistan, they can be very useful and profitable on the locations where they have been found. Theanalysis of known technologies of greenhouse heating shows the advantages and disadvantages of some of them. The aim is to get to know the soil heating technology with geothermal energy which, by its further improvement, brings considerable economic benefits.
Keywords: Geothermal energy; greenhouses; soil heating